Navigating The Escalating Climate Crisis: Comprehensive Policy Responses And Collaborative Global Action For A Sustainable Future - Maruf, Irma Rachmawati; Sari, Avid Leonardo; Saptayuda, Agusfian; Purwadi, Marsi Adi; Susilawaty, Andi (GoAcademica Research & Publishing, 2024)
The escalating climate crisis has become one of the greatest challenges of this century, having far-reaching negative impacts on the environment, human health, food security, and the global economy. The response to this crisis requires a deep understanding of the dynamics of climate change, as well as comprehensive and collaborative policies and actions at the global level. Therefore, it is important to evaluate and identify effective strategies to mitigate the impacts of climate change and move towards a sustainable future. This research aims to explore comprehensive policy responses and collaborative global action to navigate the climate crisis toward a sustainable future. The research method used is qualitative, by collecting and analyzing data from relevant research results and previous studies. The results of this research found that efforts to overcome the climate crisis require a comprehensive approach, involving strong international cooperation and synergy between development policies. Transitioning to clean energy, sustainable management of natural resources, and increasing community resilience to the impacts of climate change were identified as key strategies. Education and increasing public awareness are also important elements in supporting behavior change and community participation. Technology and innovation play a vital role in creating efficient and sustainable solutions. Finally, adequate funding and innovative funding mechanisms are needed to support the effective implementation of climate policies and initiatives.